PHOTOGRAPHIC IMAGES AS REPRESENTATION OF THE FOLK MUSIC TRADITION - Dukalska, Iveta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The present study analyses the documents obtained in a field study - photos from the family albums of the informants, representing the folk music making tradition in the period between 1920s –1960s. These photos as one of the types of communication known in culture, provides information on both the part of the local culture and the global culture in a certain time period. While researching the photos it is important to understand how truthfully the photographer has documented the events and the persons involved, what message regarding the tradition the particular photo carries. The folk music-making tradition is represented in most cases by images taken at a wedding, but also individual photos from family albums can provide the following data: 1) usage of musical instruments and the instrumentarium of the musical groups; 2) provides some indication of the musicians’ social prestige, as the musicians are always present on the photos. A special oral message is provided by the family album photos when these are combined with the interviews of field research, providing information of the family’s social situation, individual information about each musician, the importance of folk music-making traditions in the local community, along with the information about the photographer himself.The present study analyses folk music-making tradition in the cultural environment of Latvia’s countryside in 1920s – 1960s, based on the photos from the author’s personal archive and information about them.